A Quantitative Management Tool Reflecting Impact of Nutrient Enrichment from Mariculture in the Levantine Basin - Grossowicz, Michal; Tchernov, Dan; Gildor, Hezi (Frontiers in Marine Science, 2017)
Mariculture production increased significantly in recent years due to global rise in human population. However, in addition to providing food, fish farms are also a source of nutrients and antibiotics to the water column. Here, we research the nutrient pollution originating from fish cages in the Eastern Mediterranean by utilizing a Lagrangian modeling approach that followed trajectories of the water parcels. The effects of farm size and the farm’s distance from the shoreline were included in the model, and biological uptake and sinking of nutrients were incorporated into the analysis. By using computations of back-trajectories examining the water origin of strategically important shoreline areas, such as desalination plants, we were able to identify which of the proposed farm locations were potentially harmful. The results suggest that remotely-located, smaller and spatially distant farms are more preferable to limit the nutrient and antibiotic effluent resulting from mariculture activity.